2018
DOI: 10.1016/j.lrp.2017.08.005
|View full text |Cite
|
Sign up to set email alerts
|

Open strategy-making with crowds and communities: Comparing Wikimedia and Creative Commons

Abstract: In the wake of new digital technologies, organizations rely increasingly on contributions by external actors to innovate or even to fulfill their core tasks, including strategy-making processes. These external actors may take the form of crowds, where actors are isolated and dispersed, or of communities, where these actors are related and self-identify as members of their communities. While we know that including new actors in strategymaking may lead to tensions, we know little about how these tensions differ … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
74
0
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 75 publications
(76 citation statements)
references
References 61 publications
0
74
0
2
Order By: Relevance
“…Although open strategy work has incontestable advantages, it has also been argued that "the directive, focused, convergent qualities of traditional conceptions of strategy and the nonhierarchical, expansive and often divergent nature of dialogic approaches" (Heracleous, Gößwein, & Beaudette, 2018), raise tensions that are novel to organizations. While previous studies of open strategy researchers have mostly focused on shareholders, employees, or various partner communities, the newest stream of open strategy work builds on open innovation by applying the concept of crowdsourcing to strategy work (Aten & Thomas, 2016;Dobusch & Kapeller, 2018). The word "crowdsourcing" is used for multiple activities and practices that have crowd-participating elements (Estellés-Arolas & González-Ladrón- de-Guevara, 2012;Howe, 2006).…”
Section: Introductionmentioning
confidence: 99%
“…Although open strategy work has incontestable advantages, it has also been argued that "the directive, focused, convergent qualities of traditional conceptions of strategy and the nonhierarchical, expansive and often divergent nature of dialogic approaches" (Heracleous, Gößwein, & Beaudette, 2018), raise tensions that are novel to organizations. While previous studies of open strategy researchers have mostly focused on shareholders, employees, or various partner communities, the newest stream of open strategy work builds on open innovation by applying the concept of crowdsourcing to strategy work (Aten & Thomas, 2016;Dobusch & Kapeller, 2018). The word "crowdsourcing" is used for multiple activities and practices that have crowd-participating elements (Estellés-Arolas & González-Ladrón- de-Guevara, 2012;Howe, 2006).…”
Section: Introductionmentioning
confidence: 99%
“…A third area of participation is open strategy making. The leading organizations in this area have been new media companies, like Wikipedia and Creative Commons, which have engaged crowds and communities to handle strategic tasks -not only digital innovation but also strategy making itself (Dobusch and Kapeller 2017). The leading organizations in this area have been new media companies, like Wikipedia and Creative Commons, which have engaged crowds and communities to handle strategic tasks -not only digital innovation but also strategy making itself (Dobusch and Kapeller 2017).…”
Section: Diagnosis: Enable Community and Participationmentioning
confidence: 99%
“…In his commentary on the massification of strategy, Whittington (2015) describes open strategy making as a practice of openly and massively involving employees and other crowds in new ways. The leading organizations in this area have been new media companies, like Wikipedia and Creative Commons, which have engaged crowds and communities to handle strategic tasks -not only digital innovation but also strategy making itself (Dobusch and Kapeller 2017). Baptista et al (2017) note that open strategy making requires new organizational capabilities.…”
Section: Diagnosis: Enable Community and Participationmentioning
confidence: 99%
“…For instance, the temporal progression of the activities of the Wikimedia Foundation (the nonprofit that operates Wikipedia) evolved around the local/national constrains and opportunities, understood and explained by Wikipedia contributors, with Wikimedia limiting its own role in "identifying growth opportunities in key markets and coming up with ways to keep contributors satisfied" (Newstead and Lanzerotti, 2010). While raising the issue of relevance of the action modes observed in non-profit organizations for the study of enterprises, research has also suggested the use of data mining methods to better seize emerging topics (Dobusch and Kapeller, 2017).…”
Section: Open Processes and Fragile Engagementmentioning
confidence: 99%